Parallel computation of nucleotide mutation and divergence time inferred from phylogenetic tree using maximum likelihood method - Clarito, Bernard Klinch S. (2003)
This project developed a software called Nucleotide Mutation and Divergence Time Computation (Nucleotide MDT Computation) that counts the number of mutations by transition and transversion that occur between two nucleotide sequences and calculates the estimated divergence time of the species under study inferred from a phylogenetic tree. The software accepts a set of names of species together with their respective DNA sequences as its input data. In computing the number of mutations, a parallel computation is used for faster calculation. It utilized the PHYLIP programs in reconstruction the phylogenetic tree. To determine the estimated divergence time, it uses post order traversal and stack operations. With this software, it is now feasible to compute efficiently the number of mutations in a few seconds, instead of weeks if done manually